The Drosophila homologue of the Angelman syndrome ubiquitin ligase regulates the formation of terminal dendritic branches. - Lu, Y.; Wang, F.; Li, Y.; Ferris, J.; Lee, J.A.; Gao, F.B. (Human Molecular Genetics, 2009)
Angelman syndrome is a severe neurodevelopmental disorder mostly caused by loss-of-function mutations in the maternal allele of UBE3A, a gene that encodes an E3 ubiquitin ligase. Drosophila UBE3A (dUBE3A) is highly homologous to human UBE3A (hUBE3A) at the amino acid sequence level, suggesting their functional conservation. We generated dUBE3A-null mutant fly lines and found that dUBE3A is not essential for viability. However, loss of dUBE3A activity reduced dendritic branching of sensory neurons in the peripheral nervous system and slowed the growth of terminal dendritic fine processes. Several lines of evidence indicated that dUBE3A regulates dendritic morphogenesis in a cell autonomous manner. Moreover, overexpression of dUBE3A also decreased dendritic branching, suggesting that the proper level of dUBE3A is critically important for the normal dendritic patterning. These findings suggest that dendritic pathology may contribute to neurological deficits in patients with Angelman syndrome.